Commodification of sadness in digital spaces: A study of women as emotional labourers on Instagram - Niswatin Nurul Hidayati; Samira Agoro (An-Nisa’ Journal of Gender Studies, 2024)
In the postmodern era, commodification refers to the transformation of art, culture, and individual identity into tradable commodities, shifting emotional and social value into economic value and digital consumption. This study analyzes women’s engagement in the commodification of sadness on Instagram through melancholic music preferences, emotional labour in comment sections, and the influence of algorithms, influencers, and digital marketing on music consumption. The study employs netnography and thematic analysis to examine Instagram comments on Indonesian sad songs, using data from popular posts, sentiment coding, and ethical handling of public digital data. Findings show: (1) women predominantly prefer melancholic music, especially sad to very sad songs reflecting loss, waiting, and life pressure, indicating active emotional engagement as listeners; (2) women perform emotional labour by expressing heartbreak and regret in comment sections, turning private emotions into public spectacle that generates interaction and digital economic value; and (3) women are affected by music homogenization and commercialization shaped by influencers, algorithms, and digital marketing, positioning them as both agents and victims of commodified sadness. The study concludes that commodification of sadness on Instagram involves women as listeners and emotional labour actors, reinforced by algorithmic and influencer systems, transforming private emotions into publicly consumed content with economic value through engagement. This study contributes to postmodern commodification theory, gender studies, and Indonesian collectivist cultural perspectives, while encouraging critical digital awareness, algorithmic transparency, and stronger regulation of emotional data monetization in social media ecosystems.